Effects of vasoconstrictor on arterial blood pressure during minor oral surgical procedures - Abubakar M. Kaura; Babatunde O. Bamgbose; S.A.B Ogunwande; Amole I.O; Junichi Asaumi; Thomas Owobu (DiscoverSys Inc., 2018)
Objective: A majority of minor oral surgical procedures require the use of local anaesthetics containing vasoconstrictors as part of the composition. These vasoconstrictors cause some hemodynamic changes either by direct action on the cardiac muscle or by stimulation of the autonomic innervations of the heart. Depending on the concentration of the vasoconstrictor, an increased heart rate, increased force of cardiac contraction, and ultimately increased blood pressure may ensue. The aim of this study was to assess the effect of vasoconstrictors contained in local anaesthetics on arterial blood pressure during minor oral surgical procedures.Material and Methods: This was a one-year prospective, randomized, comparative study involving the assessment of blood pressure and pulse rate by using an electronic digital blood pressure monitoring device amongst consenting patients who were referred for tooth extraction. The potential research participants were randomly allocated into either the study or the control group. The study group was treated using 2% lignocaine with 1:80,000 epinephrine, while the control was treated using 2% plain lignocaine (without epinephrine). Normal or controlled-hypertensive patients between the ages of 18 to 55 years were enrolled into the study.Results: A total of 100 subjects with a mean age of 34.66Â±10.3 years participated in the study. There was no statistically significant difference in blood pressure and pulse rate between the patients in both the study group and control group.Conclusion: Optimal use of adrenaline-containing local anaesthetic does not cause a statistically significant increase in blood pressure or pulse rate.